EFFECT OF HYDROGEN ADDITION ON FLAME PROPAGATION CHARACTERISTICS THROUGH TUBE OF METHANE-AIR MIXTURES USING OPTICAL TECHNIQUE - SAID, ARKAN F. (Journal of Duhok University, 2017)
The effect of Hydrogen addition on laminar flame speed (Uf) of Methane – Air premixed mixtures using optical technique has been experimentally investigated inside a tube. the flame front location had been positioned by a photocell. The (Uf) measured at a laboratory conditions for an extensive range of equivalence ratios (F). In order to use density ratio method for the calculation of laminar burning velocity (UL), all experimental work was carried out at constant pressure (Pre-pressure period). The flame temperature (Tb) has been calculated theoretically. Mixture strength (F) and hydrogen content (RH) dependence of (UL) is represented by empirical correlation over the ranges F = (0.6-1.4), RH = (0, 0.1, 0.2, 0.3, 0.4), all at initial unburned mixture temperature Tu = 298 K and a pressure of (1 atm). In overlapping ranges, the results were found in satisfactory agreement with those previously published.